Untangling Peripheral Sympathetic Neurocircuits - Clyburn, Courtney; Andresen, Michael C.; Ingram, Susan L.; Habecker, Beth A. (Frontiers in Cardiovascular Medicine, 2022)
The sympathetic nervous system plays a critical role in regulating many autonomic functions, including cardiac rhythm. The postganglionic neurons in the sympathetic chain ganglia are essential components that relay sympathetic signals to target tissues and disruption of their activity leads to poor health outcomes. Despite this importance, the neurocircuitry within sympathetic ganglia is poorly understood. Canonically, postganglionic sympathetic neurons are thought to simply be activated by monosynaptic inputs from preganglionic cholinergic neurons of the intermediolateral cell columns of the spinal cord. Early electrophysiological studies of sympathetic ganglia where the peripheral nerve trunks were electrically stimulated identified excitatory cholinergic synaptic events in addition to retrograde action potentials, leading some to speculate that excitatory collateral projections are present. However, this seemed unlikely since sympathetic postganglionic neurons were known to synthesize and release norepinephrine and expression of dual neurochemical phenotypes had not been well recognized. In vitro studies clearly established the capacity of cultured sympathetic neurons to express and release acetylcholine and norepinephrine throughout development and even in pathophysiological conditions. Given this insight, we believe that the canonical view of ganglionic transmission needs to be reevaluated and may provide a mechanistic understanding of autonomic imbalance in disease. Further studies likely will require genetic models manipulating neurochemical phenotypes within sympathetic ganglia to resolve the function of cholinergic collateral projections between postganglionic neurons. In this perspective article, we will discuss the evidence for collateral projections in sympathetic ganglia, determine if current laboratory techniques could address these questions, and discuss potential obstacles and caveats.